A confidence-based aerospace design approach robust to structural turbulence closure uncertainty. (15th October 2022) - Gori, G.; Le Maître, O.; Congedo, P.M.
Abstract: We propose a confidence-based design approach robust to turbulence closures model-form uncertainty in Reynolds-Averaged Navier–Stokes computational models. The Eigenspace Perturbation Method is employed to compute turbulence closure uncertainty estimates of the performance targeted by the optimizer. The magnitude of the uncertainty estimates is exploited to establish an indicator parameter associated to the credibility of numerical prediction. The proposed approach restricts the optimum search only to design space regions for which the credibility indicator suggests trustworthy RANS model predictions. In this way, we improve the efficiency of the design process, potentially avoiding designs for which the computational model is unreliable. The reference test case consists in a two-dimensional single element airfoil resembling a morphing wing section in a high-lift configuration. Results show that the prediction credibility constraint has a non negligible impact on the definition of the optimal design. Highlights: The structural uncertainty in RANS turbulence closures frustrates the design effort. The Eigenspace Perturbation Method estimates the credibility of RANS predictions. A design approach robust to structural uncertainty in turbulence models is proposed. The efficiency of the design process is improved by enforcing CFD credibility.